The 9H-Fluoren Vinyl Ether Derivative SAM461 Inhibits Bacterial Luciferase Activity and Protects Artemia franciscana From Luminescent Vibriosis - Martín-Rodríguez, Alberto J.; Álvarez-Méndez, Sergio J.; Overå, Caroline; Baruah, Kartik; Lourenço, Tânia Margarida; Norouzitallab, Parisa; Bossier, Peter; Martín, Víctor S.; Fernández, José J. (Frontiers in Cellular and Infection Microbiology, 2018)
Vibrio campbellii is a major pathogen in aquaculture. It is a causative agent of the so-called “luminescent vibriosis,” a life-threatening condition caused by bioluminescent Vibrio spp. that often involves mass mortality of farmed shrimps. The emergence of multidrug resistant Vibrio strains raises a concern and poses a challenge for the treatment of this infection in the coming years. Inhibition of bacterial cell-to-cell communication or quorum sensing (QS) has been proposed as an alternative to antibiotic therapies. Aiming to identify novel QS disruptors, the 9H-fluroen-9yl vinyl ether derivative SAM461 was found to thwart V. campbellii bioluminescence, a QS-regulated phenotype. Phenotypic and gene expression analyses revealed, however, that the mode of action of SAM461 was unrelated to QS inhibition. Further evaluation with purified Vibrio fischeri and NanoLuc luciferases revealed enzymatic inhibition at micromolar concentrations. In silico analysis by molecular docking suggested binding of SAM461 in the active site cavities of both luciferase enzymes. Subsequent in vivo testing of SAM461 with gnotobiotic Artemia franciscana nauplii demonstrated naupliar protection against V. campbellii infection at low micromolar concentrations. Taken together, these findings suggest that suppression of luciferase activity could constitute a novel paradigm in the development of alternative anti-infective chemotherapies against luminescent vibriosis, and pave the ground for the chemical synthesis and biological characterization of derivatives with promising antimicrobial prospects.